No Difference in Clinical Effects When Comparing Alfredson Eccentric and Silbernagel Combined Concentric-Eccentric Loading in Achilles Tendinopathy: A Randomized Controlled Trial. Issue 10 (19th October 2021) - Habets, Bas; van Cingel, Robert E.H.; Backx, Frank J.G.; van Elten, Hilco J.; Zuithoff, Peter; Huisstede, Bionka M.A.
Background: Alfredson isolated eccentric loading and Silbernagel concentric–eccentric loading have both shown beneficial effects on clinical symptoms in midportion Achilles tendinopathy (AT), but they have never been compared directly. Purpose: To test for differences in clinical effects at 1-year follow-up between Alfredson and Silbernagel loading in midportion AT. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 40 recreational athletes were allocated to the Alfredson group (AG) or the Silbernagel group (SG). The primary outcome was the difference in the Victorian Institute of Sports Assessment–Achilles (VISA-A) at 1-year follow-up. Secondary outcomes were the visual analog scale for pain during activities of daily living (VAS-ADL) and sports activities (VAS–sports), the EuroQol 5 Dimensions instrument (EQ-5D), and global perceived effect score. Measurements were performed at baseline and 12-week, 26-week, and 1-year follow-up. Analysis was performed using a linear mixed-regression model with intervention (AG vs SG), time (12 weeks, 26 weeks, and 1 year postoperatively), and intervention-by-time interaction. Results: The VISA-A score improved for both AG and SG, from 60.7 ± 17.1 at baseline to 89.4 ± 13.0 at 1-year follow-up and from 59.8 ± 22.2 to 83.2 ± 22.4, respectively ( P < .001 for both). Because the interaction term did not significantly improve the model, we reported a treatment effect without interaction term, indicating a constant difference at each follow-up. The linear mixed model with correction for baseline VISA-A and confounders revealed a nonsignificant treatment effect (2.4 [95% CI, –8.5 to 13.3]; P = .656). In addition, after adjustment for the respective baseline values and confounders, nonsignificant treatment effects were found for the VAS-ADL (–2.0 [95% CI, –11.3 to 7.3]; P = .665) and VAS-sports (1.3 [95% CI, –12.8 to 15.3], P = .858). The EQ-5D subscales improved in both groups. After 1 year, significantly more SG participants considered themselves improved (77.3% [SG] vs 50.0% [AG]; P = .04). Conclusion: No differences in clinical effects were found between Alfredson and Silbernagel loading at up to 1-year follow-up. Both programs significantly improved clinical symptoms, and given their high adherence rates, offering either of them as a home-based program with limited supervision appears to be an effective treatment strategy for midportion AT. Registration: NTR5638 (Netherlands Trial Register number).